Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1089/cbr.2019.2978
|View full text |Cite
|
Sign up to set email alerts
|

MiR-214 Mediates Cell Proliferation and Apoptosis of Nasopharyngeal Carcinoma Through Targeting Both WWOX and PTEN

Abstract: Background: Nasopharyngeal carcinoma (NPC) was highly prevalent with poor prognosis among the patients. MiR-214 reported as an important NPC biomarker was associated with regulation of biological functions. This study aimed to investigate interactions between miR-214, PTEN, and WWOX and their effect on AKT signaling during the NPC progression. Methods: The 5-8F and 6-10B NPC cells were transfected with miR-214 inhibitor. MTT and colony formation assays were performed to assess cell proliferation. PI staining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…In the present study, bioinformatics analysis revealed that the 3′‐UTR of PTEN harbors putative miR‐214 binding sites, and subsequent experiments confirmed that PTEN is a direct downstream target of miR‐214, which is consistent with the findings of a previous study 37 . Another recent study by Han et al 38 . suggested that miR‐214 promoted the proliferation and restrained the apoptosis of NPC cells through inhibiting the expression of both WW domain‐containing oxidoreductase and PTEN.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, bioinformatics analysis revealed that the 3′‐UTR of PTEN harbors putative miR‐214 binding sites, and subsequent experiments confirmed that PTEN is a direct downstream target of miR‐214, which is consistent with the findings of a previous study 37 . Another recent study by Han et al 38 . suggested that miR‐214 promoted the proliferation and restrained the apoptosis of NPC cells through inhibiting the expression of both WW domain‐containing oxidoreductase and PTEN.…”
Section: Discussionsupporting
confidence: 91%
“…For example, miR-222 increases the invasion of ovarian cancer cells by acting on the target gene PTEN [14]. MiR-214 regulates the proliferation and metastasis of thyroid tumor cells by acting on WWOX and PTEN [15]. MiR-543 accelerates the proliferation of nasopharyngeal carcinoma cells by targeting JAM-A [16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-214 can inhibit the activity of hepatocellular carcinoma by targeting E2F3 [ 18 ]. In nasopharyngeal carcinoma, miR-214 can activate Akt signal pathway by regulating PTEN, so as to promote the proliferation activity of nasopharyngeal carcinoma cells [ 19 ]. Relevant studies have shown that miR-214 level increases significantly in a variety of tumors and can regulate Wnt/ β -catenin signaling pathway to promote cancer cell growth [ 20 – 22 ].…”
Section: Discussionmentioning
confidence: 99%